The Psychological Effects of Hormonal Treatment on Women Under IVF Treatment: A Comprehensive Review - Sri Raghavi Vasudevan; Mohanraj Bhuvaneswari (Medsci Publications, 2024)
This comprehensive review delves into the intricate world of assisted reproductive technologies (ART) and hormonal treatments, exploring their profound psychological effects on women undergoing IVF treatment. The psychological distress of infertility, combined with the demanding nature of ART, has been widely acknowledged, yet a comprehensive examination of the psychological impacts has remained elusive. This study examined the psychological repercussions of hormonal medications used in IVF, addressing the complex interplay of hormones and their effects in each stage of the IVF process. This review followed PRISMA guidelines and included studies from PubMed, Google Scholar, and ScienceDirect. A total of nine papers were collected. The findings of this study identified that depression, anxiety, mood swings, irritability, sleep disturbances, and cognitive changes were the most commonly seen medically induced psychological effects among the IVF patients. This review offers a holistic understanding of the psychological intricacies of IVF treatment, highlighting the imperative need for a more comprehensive approach to address the emotional wellbeing of individuals undergoing fertility procedures.